Development of compact and high torque 16 pole 18 slot motor for power assist legs - Yohji OKADA (The Japan Society of Mechanical Engineers, 2019)
A compact and highly efficient motor is proposed in this paper. It is intended to apply to power assist legs. The motor is flat type outer rotor motor which has 16 neodymium PM pole rotor and 18 concentrated wound slot stator. Higher torque and light weight motor is better for leg assost device. Bigger least common multiple of rotor pole and stator slot number produces higher torque and lower cogging. The motor is designed using commercial FEM analysis MagNet to optimize their dimensions. The test motor is fabricated which shows high torque compared with its size than a commercial motor.